1993
DOI: 10.1051/mmm:019930040102300
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved electron energy-loss near-edge structure analysis of a near Σ = 11 tilt boundary in sapphire

Abstract: Abstract. 2014 Spatially resolved electron energy-loss spectra have been recorded from the same E = 11 grain boundary of a high purity sapphire (03B1 -Al2O3) bi-crystal that had previously been examined by high resolution electron microscopy. The energy-loss near-edge structure (ELNES) on the aluminium L2,3 edge of the bulk 03B1 -Al2O3 is consistent with previously published X-ray absorption near-edge spectra (XANES). The presence of the grain-boundary introduces additional fine structure on the L2,3 edge, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…In SR experiments investigating the energy-loss near-edge structure [14], it was found that the transition energy from the aluminium L shell to the conduction band was reduced by more than 1 eV. Hence the latter has to be attributed mainly to a shift in the core level energy.…”
Section: Discussionmentioning
confidence: 99%
“…In SR experiments investigating the energy-loss near-edge structure [14], it was found that the transition energy from the aluminium L shell to the conduction band was reduced by more than 1 eV. Hence the latter has to be attributed mainly to a shift in the core level energy.…”
Section: Discussionmentioning
confidence: 99%
“…Larger values for the scaling factor resulted in negative intensities in the energy-loss region between 560 eV and 590 eV Higher energy-losses are influenced by thickness effects and therefore not considered here. [30] and experimental studies [6][7][8]. It provides, therefore, a powerful tool to detect changes in the local coordination of the aluminium atoms at alumina interfaces.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting difference spectrum represents the ELNES arising from the interfacial atoms. So far the spatial difference technique has been applied to grain boundaries in A1203 [6] and metal-ceramic interfaces [7,8]. Figure 2 however, were not acquired at this particular interface.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)] corresponds to a typical feature of α-Al 2 O 3 structure. [1][2][3][4][5] However, the features at 77.8, 78.3, and 79.8 eV in the Al-L 2,3 edge from the PG region [ Fig. 1(b)] do not correspond to pure α-Al 2 O 3 structure, where Al has a pure 6-fold coordination to oxygen, but are even likely to originate in a mix of 4-, 5-, and 6-fold coordinations of Al.…”
Section: Resultsmentioning
confidence: 99%